Acoustic Emission New Perspectives and Applications - Reyhanoglu, Mahmut (IntechOpen, 2022)
Structural testing and assessment, process monitoring, and material characterization are three broad application areas of acoustic emission (AE) techniques. Quantitative and qualitative characteristics of AE waves have been studied widely in the literature. This book reviews major research developments in the application of AE in numerous engineering fields. It brings together important contributions from renowned international researchers to provide an excellent survey of new perspectives and paradigms of AE. In particular, this book presents applications of AE in cracking and damage assessment in metal beams, asphalt pavements, and composite materials as well as studying noise mitigation in wind turbines and cylindrical shells.